The Howiesons Poort lithic sequence of Klipdrift Shelter, southern Cape, South Africa - (:unkn) unknown (My University, 2018)
Howiesons Poort (HP) sites, over the past decades, have provided exceptional access to anthropogenic remains that are enhancing our understanding of early modern human behaviour during the Middle Stone Age in southern Africa. Here, we analyse the technological and typological trends in the lithic record that form part of these behaviours, based on the HP sequence recently excavated at Klipdrift Shelter, located on the southern Cape coast of South Africa. This study contributes to enhance knowledge on the mechanisms of changes that occurred during the transition to the post-HP. Despite patterns of continuity observed, notably for core reduction methods, the seven successive lithic assemblages show significant changes in the typological characteristics and raw material selection but also in the relative importance of blade production over time. However, these changes are not necessarily synchronic and occur either as gradual processes or as abrupt technological shifts. Consequently, we cross-examine the association between the lithic phasing and other anthropogenic remains within the HP sequence at Klipdrift Shelter. We explore the implications of these patterns of changes in terms of cultural behaviours and population dynamics during the HP and we highlight the relationship between the different phases of the HP sequence at Klipdrift Shelter and those from other South African HP sites.
Keywords: African Research